2017
DOI: 10.1371/journal.pone.0172818
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid metabolism during sweet cherry (Prunus avium) fruit development

Abstract: To elucidate metabolism of ascorbic acid (AsA) in sweet cherry fruit (Prunus avium ‘Hongdeng’), we quantified AsA concentration, cloned sequences involved in AsA metabolism and investigated their mRNA expression levels, and determined the activity levels of selected enzymes during fruit development and maturation. We found that AsA concentration was highest at the petal-fall period (0 days after anthesis) and decreased progressively during ripening, but with a slight increase at maturity. AsA did nevertheless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…88 In addition, Liang et al showed that the pattern of ASA metabolism in kiwifruit was consistent with the changing pattern of mRNA expression levels of AO2, APX3, GR1, and DHAR1. 112 Different treatments improved the antioxidant capacity of fruits and vegetables, and there was a certain correlation between antioxidant enzymes and transcription abundance. The activity and transcription levels of SOD, CAT, APX, and GR, as well as the expression levels of AO, APX, DHAR, GR, and GST, increased, leading to a decrease in ROS accumulation.…”
Section: Effect Of Ozone Treatment On Antioxidant-related Proteins Ofmentioning
confidence: 97%
“…88 In addition, Liang et al showed that the pattern of ASA metabolism in kiwifruit was consistent with the changing pattern of mRNA expression levels of AO2, APX3, GR1, and DHAR1. 112 Different treatments improved the antioxidant capacity of fruits and vegetables, and there was a certain correlation between antioxidant enzymes and transcription abundance. The activity and transcription levels of SOD, CAT, APX, and GR, as well as the expression levels of AO, APX, DHAR, GR, and GST, increased, leading to a decrease in ROS accumulation.…”
Section: Effect Of Ozone Treatment On Antioxidant-related Proteins Ofmentioning
confidence: 97%
“…The maximum AsA content in sweet cherry (Prunus avium cultivar Hongdeng) fruits is observed during their setting followed by a gradual decrease during fruit development and a moderate increase in the mature fruit (Liang et al, 2017). Nonetheless, AsA content continues to increase with the weight of fresh fruits.…”
Section: Specific Features Of Asa Biosynthesis and Accumulation In Frmentioning
confidence: 99%
“…Full-sized cDNAs of 10 genes involved in the L-galactose pathway of AsA biosynthesis have been described as well as of 10 genes involved in AsA recycling. The expression levels of the genes encoding GDP-L-galactose phosphorylase (GGP2), L-galactono-1,4-lactone dehydrogenase (GalLDH), ascorbate peroxidase (APX3), ascorbate oxidase (AO2), glutathione reductase (GR1), and dehydroascorbate reductase (DHAR1) correlate with the quantitative content of vitamin C during fruit development, which suggests that the joint work of all these genes involved in AsA biosynthesis, degradation, and recycling together regulates the AsA accumulation in sweet cherry fruits (Liang et al, 2017).…”
Section: Specific Features Of Asa Biosynthesis and Accumulation In Frmentioning
confidence: 99%
“…As a critical metabolite in plants, AsA has several essential functions in plant physiology, participates in the detoxification of ROS, and has an important role in promoting resistance to senescence and numerous environmental stresses, such as high temperature, dehydration stress, high light, ozone, UV-B radiation, and salt stress. Also, AsA operates as a cofactor, taking part in the regulation of some fundamental cellular processes (e.g., photoprotection, the cell cycle, and cell expansion) and biosynthesis of important plant hormones (e.g., including abscisic acid, jasmonic acid, ethylene, and gibberellic acid) ( Smirnoff, 2011 ; Liang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%